In silico study of diperpens isolated from Portulaca pilosa L and their correlation with ethnobotanical studies (Research, Society and Development, 2020)
This study reports the results obtained in the in silico study for the prediction of biological activity of diterpenes present in P. pilosa, relating these results to use claims, pharmacokinetic and toxicological aspects. Several programs were used to predict biological activities, toxicity, pharmacokinetics and physical chemical properties. Prediction studies suggest that healing activity was related to friedelin, but this compound seems to be toxic, has high liposolubility and inhibits CYP. The systemic anti-inflammatory activity was related to pilosanone A and pilosanol A, when toxic, pharmacokinetic and physical-chemical aspects were analyzed, it can be suggested that pilosanol A is more promising. Pilosonone B seems to have an anti-diuretic effect, contrary to the claim of use. In silico studies suggest the antineoplastic potential of pilosonones A and B, pilosanol A and B, relating adverse effects to immunotoxicity, and all compounds evaluated seem to bind to androgen receptors, pilosanone A and B, and portulide may interfere with the prostaglandin pathway and the oxidative cleavage of alkylamines in aldehydes and ammonia. The present study corroborated the claims of healing and anti-inflammatory use of P. pilosa and suggested that the friedeline, pilosanone A and pilosanol A compounds are involved in these activities.